Analysis and modification of central carbon metabolism in Hypsizygus marmoreus for improving mycelial growth performance and fruiting body yield - Lin, Hui; Li, Pengfei; Ma, Lu; Lai, Shufang; Sun, Shujing; Hu, Kaihui; Zhang, Liaoyuan (Frontiers in Microbiology, 2023)
Hypsizygus marmoreus is one of mainly industrialized cultivation varieties of edible fungi with delicious taste and high nutritional value. However, the long harvest period with 130-150 days greatly limits its large-scale expansion. This study aimed to investigate the effects of central carbon metabolism (CCM) on the mycelial growth performance and fruiting body formation of H. marmoreus. Nine edible fungi with different harvest periods were collected and used to evaluate their intracellular carbon metabolic differences of CCM, which revealed that imbalanced distribution of intracellular carbon metabolic level in the CCM of H. marmoreus might be one of key factors resulting in slow mycelial growth rate and long harvest period. Further analysis by three strategies including metabolomics, adaptation of different carbon sources, and chemical interference confirmed that low carbon flux into pentose phosphate pathway (PPP) limited the supply of raw materials and reducing power, and thus influenced mycelial growth of H. marmoreus. Furthermore, four transformants with increased expression level of glucose-6-phosphate dehydrogenase (G6PDH), a key rate-limiting enzyme in the PPP of H. marmoreus, were developed and showed more extracellular soluble protein secretion, and higher sugar assimilation rates as well as mycelial growth rates improved in bottle substrate mixtures. Finally, cultivation experiments indicated that the maturation periods of fruiting body with about 4-5 days in advance and maximum fruiting body yield of 574.8 g per bag with an increase of 7.4 % were achieved by improving G6PDH expression level of the PPP in H. marmoreus. This work showed that CCM played an important role on mycelial growth and development of edible fungi, which provided a new insight for the breeding of edible fungi in future.